Challenges of Primary Care Medicine in a Tertiary Care Setting—The Case of Primary CMV Infection Compared to Primary EBV Infection: A Retrospective Cohort Study - Etienne, Samuel; Leuzinger, Karoline; Hirsch, Hans H.; Osthoff, Michael (Frontiers in Medicine, 2022)
Background In the immunocompetent adult primary cytomegalovirus (CMV) infection may present as prolonged febrile illness or may resemble infectious mononucleosis. Hence, establishing a diagnosis of primary CMV infection may be challenging, in particular in the hospital setting. Methods We performed a retrospective analysis of all immunocompetent patients treated at a tertiary care center in Switzerland over a 5-year period in whom a diagnosis of primary CMV infection was established. We assessed their demographic, clinical, and laboratory characteristics and compared them to patients with a diagnosis of primary Epstein-Barr virus (EBV) infection during the same period. Results We identified 16 and 125 patients with primary CMV and EBV infection, respectively (incidence of 3.1 and 23.8 cases/year, respectively). Patients in the CMV group were older (median 34 vs. 22 years), had a longer illness duration before presentation (median 14 vs. 7 days) and more frequently systemic symptoms compared to patients in the EBV group. Increased lymphocyte count and presence of atypical lymphocytes were observed in both groups, yet less frequently and less pronounced in the CMV group. The overall number of performed tests (including laboratory and radiology tests) was significantly higher in the CMV group (median 11.5 vs. 3.0) before arriving at the final diagnosis. Antibiotic treatment was more frequently prescribed in patients with primary EBV infections (40 vs. 25%). Conclusions Given its low incidence and non-specific symptoms, establishing a diagnosis of primary CMV infection can be challenging. Knowledge about clinical features of primary CMV infection in the immunocompetent host might help to adopt a stepwise approach to diagnosis avoiding over-testing.